Accelerated neuronal aging in vitro ∼melting watch ∼ - Inagaki, Emi; Yoshimatsu, Sho; Okano, Hideyuki (Frontiers in Aging Neuroscience, 2022)
In developed countries, the aging of the population and the associated increase in age-related diseases are causing major unresolved medical, social, and environmental matters. Therefore, research on aging has become one of the most important and urgent issues in life sciences. If the molecular mechanisms of the onset and progression of neurodegenerative diseases are elucidated, we can expect to develop disease-modifying methods to prevent neurodegeneration itself. Since the discovery of induced pluripotent stem cells (iPSCs), there has been an explosion of disease models using disease-specific iPSCs derived from patient-derived somatic cells. By inducing the differentiation of initialized iPSCs into neurons, disease models that reflect the patient-derived pathology can be reproduced in culture dishes, and are playing an active role in elucidating new pathological mechanisms and as a basis platform for new drug discovery. At the same time, however, we are faced with a new problem: how to accumulate age in culture dishes. It has been pointed out that cells differentiated from pluripotent stem cells are young, retain embryonic traits, and may not be fully mature. Therefore, attempts are being made to induce cell maturation, senescence, and stress signals through culture conditions. It has also been reported that direct conversion of fibroblasts into neurons can produce human neurons with an aged appearance. Here, we outline some state-pf the art insights into models of neuronal ageing in vitro. New frontiers in which stem cells and methods for inducing differentiation of tissue regeneration can be applied to aging research are just now approaching, and we need to keep a close look at these new frontiers. These models are state of the arts and intended to advance our knowledge of the molecular mechanisms of aging and to contribute to the development of therapies for human neurodegenerative diseases associated with ageing.